2011
DOI: 10.1002/14651858.cd003062.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cot-nursing versus incubator care for preterm infants

Abstract: Gray PH, Flenady V Gray PH, Flenady V.Cot-nursing versus incubator care for preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The baseline characteristics including mean age of the neonates at admission, mean gestational age during delivery, mean age at the start of phototherapy, male-female ratio, mean weight of the neonates at admission in both groups showed no significant difference ( Table-I (Table-). There is no available data for the outcome measures of episodes of cold stress or hypothermia 5 . So, data on temperature showed no significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline characteristics including mean age of the neonates at admission, mean gestational age during delivery, mean age at the start of phototherapy, male-female ratio, mean weight of the neonates at admission in both groups showed no significant difference ( Table-I (Table-). There is no available data for the outcome measures of episodes of cold stress or hypothermia 5 . So, data on temperature showed no significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…LED phototherapy provides excellent clinical outcomes. The uniformity, intensity and wavelength of emitted light results in a 28% increase in bilirubin breakdown [5][6][7][8] .…”
Section: Resultsmentioning
confidence: 99%
“…Despite innovation and an explosion in new technology in the last 3 to 4 decades, the original concept has not changed much in the last 100 years. Old and well-known problems have also not been resolved, including the spatial limitations of treating a sick newborn inside of an enclosed environment, the changes in temperature and humidity when an incubator is opened, the difficulty in achieving contact for the mother, and a lower capacity to maintain temperature compared with a newer type of unit, the radiant warmer 2. In incubators, temperature is regulated by convection.…”
Section: Introductionmentioning
confidence: 99%
“…This is a problem because warmth through radiation may lead to a high water loss, particularly in premature newborns 10. A meta-analysis trial comparing incubator and radiant warmer2 in 2009 confirmed the higher water loss associated with the latter but did not find definitive answers on which one was the superior equipment.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of evaporation, skin temperature can drop by 3˚C within a few minutes after birth. Evaporation is much higher in the case of premature newborns than that of mature babies, and may be larger than the total heat production [6]. Common causes of heat loss by preterm babies are as follows: n A high adverse relation of the body surface area to the weight in relation to the possibility of producing thermal energy, n Limited stocks of metabolic substrates, n A thin layer of subcutaneous fat as well as poorly developed muscles and other tissues involved in thermal insulation which do not provide an adequate barrier against heat loss, n The small diameter of the body makes that the volume of ambient air is less than for the diameter of an infant body born at the proper time, quantities of heat and ensures a proper body temperature, but in the case of premature babies this process is disrupted.…”
mentioning
confidence: 98%